The temporal variability of Io’s hotspots - Mura, A.; Zambon, F.; Tosi, F.; Lopes, R. M. C.; Rathbun, J.; Pettine, M.; Adriani, A.; Altieri, F.; Ciarniello, M.; Cicchetti, A.; Filacchione, G.; Grassi, D.; et al. (Frontiers in Astronomy and Space Sciences, 2024)
We investigate the variability of the power emission of Io's hotspots by using recent Juno/JIRAM infrared observations. The Jovian Infrared Auroral Mapper (JIRAM) is an imaging spectrometer which began observing Jupiter in August 2016. Although observing Jupiter's moons is not its primary objective, JIRAM can use the frequent opportunities to observe Io (up to once per orbit) to gather infrared images and spectra of its surface. The present study uses the data acquired by JIRAM during the last two years, including the location and morphology of Io's hotspots, and the temporal variability of the total output. A new photometric model for the hotspots and the dayside surface has been developed, which permits us to disentangle the temporal variability from the changes in the observation geometry. While the latitudinal dependence of the power output is not well constrained, low-latitude hotspots show a significantly more intense temporal variability and greater temperature. Key points: • New photometric model for the dayside reflected sunlight and for the hotspot emission angle dependence • Improved resolution mapping of hotspots • Characterization of Io's hotspot temporal variability: low latitude hotspots have more intense temporal variability